2021
DOI: 10.1017/s0022029921000054
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing milk osteopontin concentration based on measurements from Danish Holstein cows

Abstract: Our objective was to determine the content of the bioactive protein osteopontin (OPN) in bovine milk and identify factors influencing its concentration. OPN is expressed in many tissues and body fluids, with by far the highest concentrations in milk. OPN plays a role in immunological and developmental processes and it has been associated with several milk production traits and lactation persistency in cows. In the present study, we report the development of an enzyme linked immunosorbent assay (ELISA) for meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
(50 reference statements)
3
6
0
Order By: Relevance
“…The level of OPN in bovine milk has been estimated in several studies. A comprehensive study comprising milk from 661 Danish Holstein cows showed an average OPN concentration of 23.0 mg/L [35]. This concentration is in line with the average concentration of 18 mg/L determined for pooled dairy milk [36].…”
Section: Osteopontin In Bovine Milksupporting
confidence: 79%
“…The level of OPN in bovine milk has been estimated in several studies. A comprehensive study comprising milk from 661 Danish Holstein cows showed an average OPN concentration of 23.0 mg/L [35]. This concentration is in line with the average concentration of 18 mg/L determined for pooled dairy milk [36].…”
Section: Osteopontin In Bovine Milksupporting
confidence: 79%
“…The OPN content in the collected Jersey milk turned out to have a higher content of OPN than previously measured in bovine milk. It is of relevance to note that the LC-MS/MS method used is different from the ELISA method used in previous studies [ 48 ]. The lack of cognitive effects in the current study may lie in the fact that the control pigs already receive OPN in concentrations of 91 mg/L, as inherently present in the Jersey milk, and the additional OPN supplementation gives no additional benefits.…”
Section: Discussionmentioning
confidence: 99%
“…An in-house developed enzyme-linked immunosorbent assay (ELISA) [ 29 ] was used to quantify the levels of OPN in cell lysates. A 96-well MaxiSorp immunoassay plate (Thermo Fisher Scientific, Hillsboro, OR, USA) was coated with 0.5 μg/mL bovine milk OPN IgG in 0.1 M sodium carbonate, pH 9.8, overnight at 4 °C, washed with PBS, and blocked with 2% ( w / v ) ovalbumin in PBS for 1 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%